The Mediating Role of Mindfulness in Explaining the Causal Relationships between Psychological Well-Being, Emotion Regulation, and Family Functioning in Firefighters - Mahdavi , Masoumeh; Rezakhani, Simindokht; Janangir , Pantea (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to examine the mediating role of mindfulness in explaining the causal relationships between psychological well-being and emotion regulation with family functioning in firefighters.Methodology: The research method was correlational, using structural equation modeling (SEM). The statistical population included married firefighters who were employed in fire stations in the southwestern districts of Tehran during the winter of 2022 and spring of 2023, with a minimum of two years of work experience and at least one year of marriage. Based on the recommendations of Hoyt and Kramer, 300 participants were selected voluntarily. For data collection, the Family Functioning Questionnaire (Epstein et al., 1980), the Emotion Regulation Questionnaire (Gross & John, 2003), the Psychological Well-Being Scale (Ryff, 1989), and the Mindfulness Questionnaire (Baer et al., 2006) were used. The statistical analysis results, based on structural equation modeling, indicated that the proposed structural model had a good fit with the collected data.Findings: The indirect path coefficients between psychological well-being and the reappraisal component of emotion regulation with family functioning, as well as the total path coefficients between these variables and mindfulness with family functioning, were negative and significant. In contrast, the total and indirect path coefficients of the suppression component of emotion regulation with family functioning were positive and significant. Additionally, the findings revealed that emotion regulation, psychological well-being, and mindfulness could explain 57% of the variance in family functioning among firefighters.Conclusion: Therefore, it can be concluded that enhancing psychological well-being, increasing mindfulness, and addressing emotion regulation strategies can contribute to improving family functioning.